The Regional Development Council as a mechanism for coordination and effective performance focus on Region II - Brillantes, Alex B. Jr. (1980)
The importance of the role of local governments in the planning and implementation of national development programs has led to the formation of coordinative mechanisms that would transform these into effective instruments for development. The Regional Development Council (RDC) is one of the mechanisms tasked with coordinating the government's plans and programs in a particular area. Based on a study of Region II RDC, however, it is concluded that coordinative capacity and actual coordinative performance of the RDC have generally been weak, and as a consequence, have been less effective. It is recommended, therefore, that RDCs be strengthened particularly in terms of resources, authority and capable technical staffs if these are to function as coordinative mechanisms for the planning and implementation of development programs and projects.
Keywords: Regional planning; Regional Development Council (RDC)